Comunicación digital: una propuesta de análisis desde el pensamiento complejo (2013)
Today’s complex world of digital communication is determined by technological developments that shape new ways of constructing messages (new narratives), new dynamics for transmitting, distributing and exhibiting those messages (new media), new possibilities for languages and the media to relate to and interact with the user (new uses and appropriations), and new consumer communities created on the basis of special interests (new audiences), all in a communicative environment characterized by an oversupply of content. This paper reflects on the dynamics of digital communication in light of the paradigm of complex thinking proposed by Edgar Morin.